Constraints Perceived by the Beekeepers of Jammu Province in Adoption of Scientific Beekeeping Practices (Indian Journal of Extension Education, 2020)
Beekeeping has established itself as an economic activity and a commercial enterprise in the state of Jammu and Kashmir due to its great potential for generating the employment, additional source of income, adding food and nutritional security and improvement in rural economy. Several deviations in the form of lack of knowledge and adoption of recommended production technology are considered the limiting factors in flourishing apiculture as an enterprise in the state. The present study was conducted in four districts of Jammu province viz., Jammu, Kathua, Rajouri and Ramban in which a total of 210 beekeepers were selected to collect data regarding different constraints viz., economic, technological, infrastructural, administrative, post-harvest and socio-cultural constraints faced by the beekeepers in adoption of improved beekeeping practices. The data were collected through face-to-face interview technique. The results revealed that the major economic constraints include high cost of beekeeping equipment and low selling price of honey. The major technological constraints include lack of knowledge about honeybee enemies and new technologies while as the major administrative and infrastructural constraints included lack of state government support, non-availability of honey processing units and skilled labour. The public disputes arising due to bee sting, interference of neighbours and compulsion family members to give up the apiculture enterprise as profession were observed the major socio-economic constraints. There is an urgent need to make efforts by the state government so that the beekeepers could get rid of these constraints.